DESIGN OF A CLAP DETECTION LIGHT CONTROL SYSTEM BASED ON ARDUINO UNO - Luaha, Kesadaran; Ismail, Syahlan; Rahman, Arif; Siagian, Nurhawa Nizar; Amalia, Laily Rizky; Wijaya, Rian Farta (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
Lamp technology can also provide lighting, currently it has helped many people's activities in their daily life activities. Here the author aims to make a prototype in the form of a tool with a system that can turn on and turn off the lights, by turning off different lights and efficiency so that it no longer requires physical contact to turn them on and off. so that the lights can turn on and off by utilizing a sound from the movement of the human body that can be received directly without having to touch the switch of the lamp. In making it the author uses the Arduino Uno microcontroller as the brain of this system, with input in the form of the FC-04 sound sensor module, namely the sound sensor works based on incoming sound waves. If the sound waves hit the sensor membrane, it will have an effect on the sensor membrane vibrating. The membrane will convert sound waves into electrical quantities which can later be used as parameters to control output devices. This system is designed in such a way that it can work according to the desired features